Protocorm-like-body extract of Phalaenopsis aphrodite combats watermelon fruit blotch disease - Ho, Bo-Lin; Chen, Jhun-Chen; Huang, Tzu-Pi; Fang, Su-Chiung (Frontiers in Plant Science, 2022)
Bacterial fruit blotch, caused by the seedborne gram-negative bacterium Acidovorax citrulli, is one of the most destructive bacterial diseases of cucurbits (gourds) worldwide. Despite its prevalence, effective and reliable means to control bacterial fruit blotch remain limited. Transcriptomic analyses of tissue culture-based regeneration processes have revealed that organogenesis-associated cellular reprogramming is often associated with upregulation of stress- and defense-responsive genes. Yet, there is limited evidence supporting the notion that the reprogrammed cellular metabolism of the regenerated tissued confers bona fide antimicrobial activity. Here, we explored the anti-bacterial activity of protocorm-like-bodies (PLBs) of Phalaenopsis aphrodite. Encouragingly, we found that the PLB extract was potent in slowing growth of A. citrulli, reducing the number of bacteria attached to watermelon seeds, and alleviating disease symptoms of watermelon seedlings caused by A. citrulli. Because the anti-bacterial activity can be fractionated chemically, we predict that reprogrammed cellular activity during the PLB regeneration process produces metabolites with antibacterial activity. In conclusion, our data demonstrated the antibacterial activity in developing PLBs and revealed the potential of using orchid PLBs to discover chemicals to control bacterial fruit blotch disease.